Prevalence and antimicrobial resistance profile of Escherichia coli O157:H7 in goat slaughtered in Dire Dawa Municipal Abattoir as well as food safety knowledge, attitude and hygiene practice assessment among slaughter staff, Ethiopia - Dulo, F. (Addis Ababa University, 2014)
Escherichia coli O157:H7 serotype is worldwide zoonotic pathogens responsible for the majority of severe cases of human enterohemorrhagic Escherichia coli (EHEC) disease. The aim of this study was to investigate the prevalence and antimicrobial resistance pattern of E. coli O157:H7 in goat slaughtered at Dire Dawa municipal abattoir, Ethiopia. A total of 235 samples were collected from cecal contents, carcass and environment sample (slaughter house worker’s hand, knife and carcass wash water) as 93, 93 and 49, respectively through the months of January and April. E. coli O157:H7 was identified by the method slightly modified to ISO 16654:2001.The samples were initially enriched in modified trypticase broth containing novobiocin supplement, followed by plating onto sorbitol MacConkey agar. Consequently, the suspected non-sorbitol fermenting (NSF) colonies were confirmed as E. coli biochemically using indole test and selected for serotyping. Out of 235 samples collected, the overall prevalence of 2.55% (comprising of 2.15%, 3.22% and 2.04 of cecal contents, carcass swab and environmental samples respectively) had positive results for Dryspot E. coli O157 latex test kit (Oxoid, DR120M). Eighteen different antibiogram belonging to 10 pharmacological groups including ampicillin, amoxycillin-clavulanic acid, cefotaxime, ceftriaxone, cefoxitin,cefuroxime Sodium, chloramphenicol, ciprofloxacin, erythromycin, gentamicin, kanamycin, nalidixic acid, nitrofurantoin, norafloxacin, streptomycin, sulfamethoxazole-trimethoprim, sulfonamides cpds, tetracycline were used for antimicrobial susceptibility test. Resistance to erythromycin was noted in all of the isolates (100%, n=6/6). Most of E. coli O157:H7 isolates also showed high resistance to ampicillin (83.3%, n=5/6) and moderate resistance to nitrofurantoin (50%, n=3/6). All the isolates were resistant to at least two of the antibiotics tested. No isolated E. coli O157:H7 strain resistance noted to cefotaxime, ceftriaxone, cefuroxime sodium, chloramphenicol, ciprofloxacin, gentamicin nalidixic acid and norfloxacin. This study concludes that the occurrence of E. coli O157:H7 and E. coli O157:H7 multiple antibiotic resistant profiles in goat slaughtered at Dire Dawa municipal abattoir and this may show a risk for public health and food safety. Regulatory control of antibiotics usage in livestock production, meat hygiene and pharmaco-epidemiological surveillance in food animals is hereby recommended to ensure consumer safety.